2012
DOI: 10.2106/jbjs.k.00531
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a Thrombin-Based Hemostatic Agent in Unilateral Total Knee Arthroplasty

Abstract: The present study showed that Floseal had no demonstrable effect on blood loss as measured through drain output following total knee arthroplasty. There were also no notable adverse events associated with its use. The usefulness of Floseal as a hemostatic agent in total knee arthroplasty remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 8 publications
0
56
1
1
Order By: Relevance
“…- 14 In the context of orthopedic surgery, and especially in knee surgeries , its effectiveness is still controversial , with few and limited studies on the subject. Kim et al 18 showed no significant differences using or not the product in unilateral knee arthroplasties. However, Comadoll et al 20 showed that the use of Floseal (r) can significantly reduce the postoperative hemoglobin level drop, although it has not cause differences in the rates of blood transfusions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…- 14 In the context of orthopedic surgery, and especially in knee surgeries , its effectiveness is still controversial , with few and limited studies on the subject. Kim et al 18 showed no significant differences using or not the product in unilateral knee arthroplasties. However, Comadoll et al 20 showed that the use of Floseal (r) can significantly reduce the postoperative hemoglobin level drop, although it has not cause differences in the rates of blood transfusions.…”
Section: Discussionmentioning
confidence: 96%
“…This compound has already made significant benefits to control bleeding in several medical applications, 11 - 14 including orthopedic surgery, 5 - 17 but has not proven to be particularly efficient in total knee arthroplasty 18 . The primary objective of this work is to assess whether hemostasis with electrocautery compared to Floseal (r) during primary total knee arthroplasty leads to different rates of perioperative bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Randomization was determined before surgery through a sealed opaque envelope system (''Yes'': Evicel, ''No'': control group [8]. Envelopes were opened after the cementing of components.…”
Section: Methodsmentioning
confidence: 99%
“…For calculation of sample size, the following inputs were used as described in an earlier study [8]: 80% power, a critical p value of 0.05, and a mean difference and SD of 150 ± 350 mL of drain output. A sample size of 98 subjects per group was calculated to give a post hoc power of 85% to detect differences in drainage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation